Evolving Document Patterns in UK Research Assessment Cycles - Adams, Jonathan; Gurney, Karen; Loach, Tamar; Szomszor, Martin (Frontiers in Research Metrics and Analytics, 2020)
Researcher behaviour is shown to change under assessment. An unexpected time-skew towards most recent papers in each census period was found among the outputs selected by UK academics for the research assessment cycles of the 1990s. This skew changed to a more even time-based distribution for scientists and engineers in later cycles. At the same time engineers switched their preferred output type for submission, from conference proceedings to journal articles. Social scientists also switched, from monographs to journal articles. There was no discussion of these output patterns at the time, or later, but the patterns and their evolution had marked consistency across subjects and institutions. These changes are discussed in terms of consensus and influences on researcher concepts of the evidence of excellence. The increasing availability of citation data in the 1990s and the likely role of citation analysis as a steering factor is noted.